2019
DOI: 10.1029/2019jd031295
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Increase in Regional Evaporative Water Consumption as a Result of Vegetation Restoration Over the Loess Plateau, China

Abstract: One of the world's largest revegetation programs, the Grain for Green Project (GfGP), has been taking place on the Loess Plateau of China since 1999. Such massive revegetation causes changes in the region's hydrological cycle, water availability, and ecological sustainability through enhanced evapotranspiration (ET). Here we quantify effects of the GfGP's revegetation on ET over this water-stressed region. Our approach involves use of a modified Priestley-Taylor Jet Propulsion Laboratory (PT-JPL) model, incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 94 publications
(119 reference statements)
8
63
0
Order By: Relevance
“…The spatial patterns of modeled mean annual ET and the percentage of ET components were shown in Figure 5. Generally, the annual ET over the study region exhibited large spatial heterogeneity and showed gradients increasing from the northwestern parts to the southeastern parts, which was consistent with previous studies (Jin et al, 2017; Shao et al, 2019). Annual ET was generally higher than 400 mm yr −1 in the mountainous and southeastern plateau where forest and irrigated cropland were distributed (Figure 5a).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The spatial patterns of modeled mean annual ET and the percentage of ET components were shown in Figure 5. Generally, the annual ET over the study region exhibited large spatial heterogeneity and showed gradients increasing from the northwestern parts to the southeastern parts, which was consistent with previous studies (Jin et al, 2017; Shao et al, 2019). Annual ET was generally higher than 400 mm yr −1 in the mountainous and southeastern plateau where forest and irrigated cropland were distributed (Figure 5a).…”
Section: Resultssupporting
confidence: 91%
“…For the long-term sustainability of water resources, vegetation restoration and agricultural land management should fully consider local water resources, as the current vegetation cover has already approached sustainable water resource limits (Feng et al, 2016;Liang et al, 2019). Future climate scenarios showed that the increasing rate of precipitation was similar to that of ET (Shao et al, 2019), which can maintain a Figure 16. Causal network.…”
Section: 1029/2020jd033380mentioning
confidence: 99%
See 1 more Smart Citation
“…Through the analysis of the four climate change scenarios, the overall trends are relatively consistent. Relevant studies mostly use SSP370 as a representative model to analyze climate change (Shao et al, 2019;Butchart et al, 2020). This study also used the SSP370 model to analyze the snowfall trend of the Huaihe River Basin.…”
Section: Analysis Of the Evolution Of Snowfall Under Climate Change Smentioning
confidence: 99%
“…Vegetation can regulate water yield by changing water and heat conditions of the underlying surface and is also key element of ecosystem (Creed et al, 2014; Farley et al, 2005; Wei et al, 2018; Woodward et al, 2014; Zhang et al, 2020; Zhang, Yang, McVicar, & Yang, 2018). In recent years, vegetation dynamics have been significantly influenced by the large‐scale ecological rehabilitation, especially in China's inland rivers (Cheng et al, 2014; Feng et al, 2015; Shao et al, 2019). However, it is still not clear to what extent vegetation dynamics influence the balance between ecological stability and water yield in the upstream, partly due to the sparseness of monitoring data which can be used to quantify regional vegetation dynamics.…”
Section: Introductionmentioning
confidence: 99%